Variations of geomagnetic response functions in Japan - I.I. Rokityansky; V.I. Babak; A.V. Tereshyn (Геофизический журнал, 2015)
Peculiarities of measurements have been described for response functions (RF), historical review of RF application in Japan has been given together with general condition of earthquake forecast (EQ). Detailed analysis of vast material of processing obtained under conditions of strong disturbances has been fulfilled. Anomalies of response functions have been distinguished, which occurred during several years before catastrophic EQ Tohoku, which might be most probably recognized as medium-term precursors of that EQ. Anomaly of electric conductivity has been revealed under the central part of Boso peninsula (Tokyo suburb) in the area of complicated joint of three lithosphere plates.